The effect of non-financial performance on financial performance moderated by information disclosure - Veranda Aga Refmasari; R A Supriyono (Journal of Economics, Business, and Accountancy Ventura, 2019)
This research aimed to test the effect of non-financial performance on financial performance moderated by information disclosure. Balance scorecard was used to measure performance values in a comprehensive, coherent, measurable, and balanced. The research result showed that non-financial performance measures consisting of consumer, learning and growth perspectives affected financial performance, but internal business process did not affect financial performance. With cause-effect, learning and growth affect internal bussines process, and the internal business process affects customers Information openess does not has efffect of non-financial performance relationship towards financial performance. This research suggests that companies need to increase customer satisfaction and employee-based and strategic alignment growth to improve the company's financial performance.